2023
DOI: 10.3390/molecules28155812
|View full text |Cite|
|
Sign up to set email alerts
|

Antimicrobial, Antibiofilm, and Anticancer Activities of Syzygium aromaticum Essential Oil Nanoemulsion

Abstract: In the current study, clove oil nanoemulsion (CL-nanoemulsion) and emulsion (CL-emulsion) were prepared through an ecofriendly method. The prepared CL-nanoemulsion and CL-emulsion were characterized using dynamic light scattering (DLS) and a transmission electron microscope (TEM), where results illustrated that CL-nanoemulsion droplets were approximately 32.67 nm in size and spherical in shape, while CL-nanoemulsion droplets were approximately 225.8 nm with a spherical shape. The antibacterial activity of CL-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(8 citation statements)
references
References 73 publications
1
7
0
Order By: Relevance
“…The increased contrast observed at the interface of the oil droplets can be attributed to the affinity of uranyl acetate, which is utilized as a negative staining agent, toward the components present at the interface. The obtained results are in full agreement with the results obtained by Shehabeldine et al, who prepared a clove oil nanoemulsion so as to enhance its antimicrobial and anticancer activity, and they found that the TEM image of the prepared clove oil nanoemulsion was spherical in shape [59].…”
Section: Transmission Electron Microscopy (Tem) Of Ginger Oil Nanoemu...supporting
confidence: 91%
“…The increased contrast observed at the interface of the oil droplets can be attributed to the affinity of uranyl acetate, which is utilized as a negative staining agent, toward the components present at the interface. The obtained results are in full agreement with the results obtained by Shehabeldine et al, who prepared a clove oil nanoemulsion so as to enhance its antimicrobial and anticancer activity, and they found that the TEM image of the prepared clove oil nanoemulsion was spherical in shape [59].…”
Section: Transmission Electron Microscopy (Tem) Of Ginger Oil Nanoemu...supporting
confidence: 91%
“…The applied hot steam is the main cause of the bursting and rupture of the cellular structure of the plant matrix. Consequently, EOs are released from the plant material until they reach a cooled condenser that causes the vapor to condense again into a liquid, formed by two immiscible phases: water and EOs [73,75], which can be separated using a Clevenger apparatus, a separation funnel, or other equipment [76].…”
Section: Conventional Methodsmentioning
confidence: 99%
“…Green synthesis, also known as biosynthesis, is an inexpensive technique that is clean, safe, biocompatible, and environmentally friendly ( Lashin et al, 2023 ; Shehabeldine et al, 2023 ). This process uses biological entities to reduce, cap, and stabilize metal or metal oxide precursors to form nanoparticles (NPs): bacteria, actinomycetes, yeast, fungi, algae, and plant extract ( Dikshit et al, 2021 ; Albalawi et al, 2022 ; Hashem and El-Sayyad, 2023 ; Hashem et al, 2023c ).…”
Section: Introductionmentioning
confidence: 99%